2010
DOI: 10.1088/0031-8949/83/01/015401
|View full text |Cite
|
Sign up to set email alerts
|

The incoherent pump rate: an optical tool for controlling the probe response and dispersion in a three-level Λ system in the presence of spontaneously generated coherence

Abstract: The probe response and dispersion of a three-level closed system considering spontaneously generated coherence (SGC) have been investigated with and without an incoherent pumping. One can get electromagnetically induced transparency (EIT) whatever be the value of the SGC parameter and phase difference when an incoherent pump is absent. But by turning the incoherent pump rate on, one can control the light propagation from subluminal to superluminal and also the nonlinear response from EIT to electromagnetically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Several researchers attempted to demonstrate experimentally in subluminal [31,32,[94][95][96][97] and superluminal [98][99][100][101] lights. Recently, studies have also been done on the switching between the subluminal and superluminal propagations in an atomic medium by changing frequency, intensity, phase and polarization of applied fields [57,58,[102][103][104][105][106][107][108][109][110]. Moreover, some research groups used multiple EIT to control the group velocity at multiple frequencies [42,46,[56][57][58].…”
Section: Controlling Group Velocity Of Multi-frequency Lightmentioning
confidence: 99%
“…Several researchers attempted to demonstrate experimentally in subluminal [31,32,[94][95][96][97] and superluminal [98][99][100][101] lights. Recently, studies have also been done on the switching between the subluminal and superluminal propagations in an atomic medium by changing frequency, intensity, phase and polarization of applied fields [57,58,[102][103][104][105][106][107][108][109][110]. Moreover, some research groups used multiple EIT to control the group velocity at multiple frequencies [42,46,[56][57][58].…”
Section: Controlling Group Velocity Of Multi-frequency Lightmentioning
confidence: 99%
“…On this basis, extremely slow or superluminal light pulses were obtained in the EIT [7][8][9] or EIA [10][11][12] regime, respectively. In particular, some recent studies have shown that it is possible to switch between EIT and EIA modes [13] and thus can switch between fast light and slow light by external fields such as using microwave field [14], standing-wave field [15], Kerr field [16][17][18], coherent pump field [19,20], incoherent pump field [21][22][23], static magnetic field [24,25], or using other coherence effects such as spontaneously generated coherence [22,23,[26][27][28][29] and the phase of applied laser fields [30,31] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Simplest exciting schemes of the EIT are three-level atomic systems consisting of Λ-type [5], V-type [6], and ladder-type [7] configurations. The EIT materials have interesting applications in the fields of quantum and nonlinear optics including lasing without population inversion [8], slow and fast light [9][10][11][12], enhancement of Kerr nonlinearity [13][14][15][16][17][18][19][20][21][22][23], controlling optical bistability [24][25][26][27], pulse propagation [28][29][30], all-optical switching [31,32], and so on. The studies demonstrated that the linear and nonlinear optical properties of materials are easily controlled according to the intensity, frequency, polarization, and phase of external light fields.…”
Section: Introductionmentioning
confidence: 99%